THE FEELINGS OF CONTROL INDUCED BY PSYCHOLOGICAL INTERVENTIONS IN CANCER PATIENTS: ARE THEY THE MAIN KEY TO EXPLAIN THE EFFICACY OBSERVED? - Bárez, Milagros; Blasco, Tomás; Fernández Castro, Jordi (Anales de Psicología / Annals of Psychology, 2003)
Studies of psychological interventions in cancer patients developed since 1990 are reviewed. In spite of the different approachs used, it is speculated that the main resource to coping with cancer stress could be the induction of feelings of control in the patients. Feelings of control could be achieved by enhancing self-efficacy or by reducing unpredictibility. Although the avaliable data agree with our suggestion about the role of feelings of control in enhancing psychological well-being and quality of life in cancer patients, no causal relationships can be stated before developing new studies specifically addressed to confirm this possibility by using proper research-controlled designs.